Modeling of multimaterial hybrid joints under high-rate loading. (October 2020) - Ledford, Noah; May, Michael
Joint failure plays a key role in determining structural stability and crash or impact response. Characterizing the joints at high loading rates is challenging as oscillations are often overlaid on the measured data, making interpretation of the results more difficult. This paper builds upon the experimental testing three different mixed-material joints using a split-Hopkinson tension bar. The correction proposed in this work is verified using a finite element model of the entire testing system. The modeling efforts also investigate the differences in a specimen only model and a model including the entire testing system. The failure mechanisms of bolted and bonded joints are investigated, where the substrate stress state is found to play a large role in determining the failure mode for bolted joints. This work lays the foundations needed to investigate the mixed-material bolted and bonded joints in detail.